Pengembalian Uang Korupsi oleh Koruptor Kecil agar tidak Dipidana dalam Perspektif Asas Kepastian Hukum - Fera Ardilawati; Suwari Akhmaddhian (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2019)
In Indonesia, not infrequently the law is now used as a tool to strengthen power. The law is used as a tool for people's oppression and fluency in achieving a goal. The existence of the principle of legal certainty becomes the regulator of individuals and the government and serves as a benchmark for attitudes and what can and may not be done. Legal certainty becomes a limiting rope so that the government does not make the power they have to oppress the people. With the existence of legal certainty, the people will be safe and become a barrier for right and wrong behavior. The purpose of the law that approaches certainty is legal certainty. Something that is certain so that there is no doubt and become a benchmark for law enforcement. However, legal certainty sometimes becomes polemic because this principle is contrary to the principle of justice. Someone who is guilty must be punished based on the crime and offense they committed. With this principle government officials and officials cannot arbitrarily decide on something of their own free will but must go through a regulated legal process.Keywords: The principle of legal certainty, corruption, criminal AbstrakDi Indonesia, tidak jarang hukum kini dijadikan sebagai alat untuk memperkokoh kekuasaan. Hukum dijadikan sebagai alat penindas rakyat dan kelancaran dalam mencapai sebuah tujuan. Adanya asas kepastian hukum menjadi pengatur individu dan pemerintah dan menjadi tolak ukur sikap dan apa yang boleh dan tidak boleh dilakukan. Kepastian hukum menjadi tali pembatas agar pemerintah tidak menjadikan kekuasaan yang mereka punya untuk menindas rakyat. Dengan adanya kepastian hukum rakyat akan menjadi aman dan menjadi pembatas atas perilaku yang benar dan salah. Tujuan hukum yang mendekati kepastian adalah kepastian hukum. Sesuatu yang pasti sehingga tidak ada keraguan dan menjadi tolak ukur penegakan hukum. Akan tetapi kepastian hukum terkadang menjadi polemik karena asas ini bertolak belakang dengan asas keadilan. Seseorang yang bersalah harus dihukum berdasarkan kejahatan dan pelanggaran yang mereka lakukan. Dengan adanya asas ini pejabat dan aparat pemerintah tidak bisa dengan seenaknya memutuskan sesuatu dengan kehendak dirinya akan tetapi harus melalui proses hukum yang telah diatur.Kata Kunci : Asas kepastian hukum, korupsi,pidana.